THE Collembola poduromorpha FAMILIES: NEANURIDAE AND ODONTELLIDAE OF SOME LOCALITIES OF NORTHEASTERN ALGERIA (Sciences & Technologie. C, Biotechnologies, 2014)
A list of the 17 species of Collembola belongs to two sub-families of Neanuridae (Frieseinae and Pseudachorutinae) also to family of Odontellidae. The made list indicates that Frieseinae is particularly diverse with six species of the genus (Friesea). The Pseudachorutinae include 7 species, most of species met previously known in the Europe-Mediterranean region. The Odontellidae are represented by 4 species new for Algeria and al North African region. The most unexpected character of this fauna is the presence of endemic species and known only in African’s American’s tropics.